Trade Agreements, Uncertainty & Capital Structure of Exporters - Lopatin, Nikita (International Journal of Economics and Financial Issues, 2020)
This paper examines the role of export market uncertainty in the financing decisions of firms. To evaluate the effect of uncertainty reduction, I use the free trade agreement between Colombia and the USA that came into force in May 2012. Using firm-level data, and a diff-in-diff methodology, I find empirical evidence that Colombian firms that exported agricultural products to the USA experienced a decline in their leverage after the agreement’s implementation. I further disaggregate the composition of liabilities to find that the source of decline was borrowing from financial institutions. I develop an oligopoly competition model with product market uncertainty where the source of uncertainty is embedded in a firm’s profit function. The model predicts that the reduction in uncertainty leads to the decline in borrowing. The results of this paper suggest that trade agreements can benefit exporters in developing countries with imperfect capital markets where borrowing is costly. Keywords: capital structure, uncertainty, trade agreements, trade cost JEL Classifications: D22, F10, F14, G32 DOI: https://doi.org/10.32479/ijefi.8957